Pengurangan Asam Fitat Biji Kedele dengan Cara Pengupasan - Agus Setyono; Zuheid Noor; Slamet Sudarmadji; Mochamad Adnan (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 1990)
Attempts have been made to reduce phytic acid level in soybean by mechanical dehulling process. Dehulling was carried out mechanically by using abrassive roller at of 750 to 1450 rpm. for 10 to 30 seconds. Mechanical dehulling at 750 rpm for 25 seconds was able to reduce approximately 81 per cent of the original content of phytic acid This hulling procedur gave about 87 per cent recovery of the hulled soybean.